Study on the Impact of Polymer Concentration and Coagulation Bath Temperature on the Porosity of Polyethylene Membranes Fabricated Via TIPS Method - Akbari, Ali; Yegani, Reza (Journal of Membrane and Separation Technology, 2012)
Microporous high density polyethylene flat membranes were fabricated via thermally induced phase separation (TIPS) method. Effects of polymer concentration and coagulation bath temperature on the membrane morphology and porosity were investigated. To the best of our knowledge, there is no work about the order of magnitude and degree of importance of influential parameters and their interactions on the microstructure of fabricated membranes. The results showed that the porosity of membranes decreased as the polymer concentration increased. It was also shown that, due to the short contact time and rapid phase inversion between coagulation bath and membrane’s outer surfaces, bath temperature mainly affects on the outer surface porosity. The results obtained from analysis of variance (ANOVA) using 95% confidence interval on the membrane porosity revealed that the effect of polymer concentration is more important than coagulation bath temperature.